Nivel narrativo, status, persona y tipología de las narraciones - José Ángel García Landa (Miscelánea: A Journal of English and American Studies, 1996)
This paper is an interpretation and a critique of the narratological concepts of narrative level and narrative person as defined by Genette, Bal and other theorists. These concepts are placed on a firmer ground by relating them to a wider semiotic theory, especially to the theory of enunciation. The structure of narrative relies on the enunciative construction of textual subjects and on the story’s ability to convey multiple enunciations which can be used to motivate its discursive structure. Some of the main narrative positions (first-person narration, witness narration, reliable and unreliable authorial narration) are examined from this perspective. The concept of metalepsis or frame-break is also redefined.